Gender Roles And Representations In "Thakurmar Jhuli": The Role Of Witches And Colorism - Sayan Mukherjee; Rituparna Chakraborty (Educational Administration: Theory and Practice, 2024)
"Thakurmar Jhuli," a key part of Bengali folk writings by Dakshinaranjan Mitra Majumder, gives a look into the cultural and social habits of early 20th century Bengal. This study looks at the gender roles and images in these tales, focusing on how witches (dainis) are shown and the common practice of colorism. By examining how female characters, especially witches, are depicted and how colorism supports standard beauty ideas, this analysis reveals the hidden messages about gender and looks found in Bengali folklore.